The Role of Women as Educators - Imamuddin, M.; Andryadi, Andryadi; M, Zaharuddin; Isnaniah, Isnaniah; Susanti, Weti; Rehani, Rehani; Zulmuqim, Zulmuqim; Nurdin, Syafruddin (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2020)
In the Al-Qur’an and Hadith there are not prohibition for women in seeking knowledge. On the contrary, Islam requires or obliges women to seek knowledge as well as men. Science is like light that will illuminate women's footsteps into the future. A woman of knowledge must be elevated. Conversely, women who are ignorant and lack knowledge will only be considered as weak creatures who can be empowered, not empowered. Such is the importance of parent's knowledge, especially the knowledge of a woman (mother) who is able to make a child's soul character and character, good or bad, so that the obligation for children's education is directed at both parents when the child is still in the womb until he reaches adulthood. For this reason it is important for a woman (mother) have to be smart, so that the character of the mother descends on her children. As a woman (mother) who is assigned to be the first teacher for her children does not necessarily teach only what she knows, mothers who are able to give birth an intelligent generation for the homeland and nation must also have intelligence in themselves, for a woman is not wrong if have a high education in order to educate their children.